The Role of Flow in Dissemination of Recommendations for Hedonic Products in User-Generated Review Websites. Issue 3 (7th February 2020) - Argyris, Young Anna; Muqaddam, Aziz; Liang, Yuyang
ABSTRACT: The widely publicized impact of user-generated review (UGR) sites on sales has spawned a large number of studies on user behaviors on UGR sites. These existing studies center on conversions of visitors into paying customers, and the creation and dissemination of online reviews. UGR site visitors will consider emotional cues in reviews more seriously if the product offered is more enjoyment-based, hedonic, than utilitarian. This study examines the impact of user enjoyment, when reading reviews on hedonic products, on dissemination of those reviews with their personal social circles. Specifically, to examine user enjoyment on UGR sites, we apply the concept of flow – enjoyable experiences that are intense and enticing enough to convert visitors to endorsers. We conducted two online surveys to contrast our suggested flow-based explanation on dissemination against alternative rationality-based one. The findings from our surveys show that the flow state increases their intentions to recommend the establishments, while the objectivity of reviews and expertise of reviewers are limited in explaining such.